A study on knowledge, attitude and practice regarding blood donation in an urban community, Chennai - Anand N; Pugazhendiinban Pugazhendiinban (Public Health Review: International Journal of Public Health Research, 2018)
Background: Blood transfusion plays a vital role in saving the life of those patients requiring transfusion. Assessment of awareness, attitude and practice regarding blood donation will help in creating effective health education strategy to enhance blood donation.Objectives: To assess the knowledge, attitude, and practices regarding blood donation among individuals aged 18-60 years in an urban community of Chennai and to identify the factors associated with blood donation.Methods: A cross-sectional study was carried out in pudupet on the months of May and June, 2017. Table of random numbers was used to recruit a total of 300 study participants. A pilot tested semi structured, questionnaire was employed as a data collection tool. Multiple logistic regression analysis was used to examine association between the independent variables and the dependent variables.Results: Among our study subjects, 45% of them had good knowledge on blood donation and 44% of our subjects had a correct attitude towards blood donation. Only 33.3% of them had good practices towards blood donation. The most common reason quoted for not donating blood was that they were more bothered about their own health which by donating blood would lead on to some health problems.Conclusion: The present study shows an average prevalence of knowledge and attitude among the study subjects whereas when it comes to practice it was found to be less. There should be a regularly scheduled awareness creation and voluntary blood donation campaigns organized at the community level.